Pressure-Induced Phase Transformations - Errandonea, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a printed edition of the Special Issue of Crystals entitled Pressure-Induced Phase Transformations. It includes selected articles on the behavior of matter under high-pressure and high-temperature conditions, describing and discussing contemporary achievements, which were selected based on their relevance and scientific quality.